2022
DOI: 10.2217/nnm-2022-0173
|View full text |Cite
|
Sign up to set email alerts
|

Porous Se@Sio 2 Nanoparticles Improve Oxidative Injury to Promote Muscle Regeneration Via Modulating Mitochondria

Abstract: Background: Acute skeletal muscle injuries are common among physical or sports traumas. The excessive oxidative stress at the site of injury impairs muscle regeneration. The authors have recently developed porous Se@SiO2 nanoparticles (NPs) with antioxidant properties. Methods: The protective effects were evaluated by cell proliferation, myogenic differentiation and mitochondrial activity. Then, the therapeutic effect was investigated in a cardiotoxin-induced muscle injury rat model. Results: Porous Se@SiO2 NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The targeted polyphenol delivery by drug carriers created using nanotechnology that guarantees target specificity can overcome the drawbacks, and boost the bioavailability and stability of the therapeutic molecules in vivo [ 251 ]. Moreover, researches show that porous Se@SiO2 nanoparticles which would slowly release selenium could improve oxidative injury to promote muscle regeneration via modulating mitochondria [ 253 ]. CoQ’s lack of aqueous solubility and poor oral bioavailability contribute to suboptimal results observed with respect to the effect of CoQ supplements on statin-induced myopathy.…”
Section: Therapeutic Strategies Targeting Mitochondria For Skeletal M...mentioning
confidence: 99%
“…The targeted polyphenol delivery by drug carriers created using nanotechnology that guarantees target specificity can overcome the drawbacks, and boost the bioavailability and stability of the therapeutic molecules in vivo [ 251 ]. Moreover, researches show that porous Se@SiO2 nanoparticles which would slowly release selenium could improve oxidative injury to promote muscle regeneration via modulating mitochondria [ 253 ]. CoQ’s lack of aqueous solubility and poor oral bioavailability contribute to suboptimal results observed with respect to the effect of CoQ supplements on statin-induced myopathy.…”
Section: Therapeutic Strategies Targeting Mitochondria For Skeletal M...mentioning
confidence: 99%
“…Based on this, we can prepare drugs with antioxidant properties such as selenium, 184 melatonin, 185 angiotensin II antagonist, 178 and acetylcysteine 178 by wrapping them with nanomaterials and using MNs as a carrier to improve the oxidative environment at the site of injury. Yu–Xia Yang et al 186 prepared porous Se@SiO 2 NP by encapsulating Se element with SiO 2 , allowing the slow release of Se from the porous material to attenuate its toxicity. Also, it has been confirmed that the mitochondrial function and high level of oxidative environment were improved in the rat models via intraperitoneal injection.…”
Section: Application Of Mns In the Musculoskeletal Systemmentioning
confidence: 99%